1958
DOI: 10.1139/v58-003
|View full text |Cite
|
Sign up to set email alerts
|

Equivalent Orbitals and the Shapes of Excited Species

Abstract: The electron distributions in the ground states of C?H?, HCO, and NH?, and in one excited state of each species, have been considered by transforming the sinlple molecular orbitals into equivalent ones. I n the light of these considerations, the shapes and dimensions of the above species in these states have been discussed. I t is found that a considerable degree of understanding can be achieved though there is uncertainty in the interpretation in some cases. INTRODUCTIONThe object of this paper is to discuss … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1960
1960
2005
2005

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…The electronic structure of CO has been examined theoretically (186,203), and it suggested that the bonding hybrid from carbon is approximately a tetrahedral hybrid (203); this estimate places 75 per cent s character in the orbital occupied by the lone pair on carbon. The electronic structure of N2 has been compared with those of CO (219,222) and C2H2 (178). A close similarity is observed in the computed molecular orbitals for N2 and CO (260) and in the derived electron overlap populations (219,221).…”
Section: Isoelectronic Families V Localized Molecular Orbitalsmentioning
confidence: 86%
See 1 more Smart Citation
“…The electronic structure of CO has been examined theoretically (186,203), and it suggested that the bonding hybrid from carbon is approximately a tetrahedral hybrid (203); this estimate places 75 per cent s character in the orbital occupied by the lone pair on carbon. The electronic structure of N2 has been compared with those of CO (219,222) and C2H2 (178). A close similarity is observed in the computed molecular orbitals for N2 and CO (260) and in the derived electron overlap populations (219,221).…”
Section: Isoelectronic Families V Localized Molecular Orbitalsmentioning
confidence: 86%
“…In the previous section, the valence electrons about an atom in a molecule wore pictured in localized orbitals. The advantages of partitioning the electron cloud of a molecule into localized, nonoverlapping parts, called in molecular orbital theory equivalent, orbitals, have been discussed by several authors (48,112,120,161,163,178,247,271). Two types of localized orbitals are frequently encountered: orbitals occupied by unshared, nonbonding electrons, and orbitals occupied by bonding or shared electrons.…”
Section: Isoelectronic Families V Localized Molecular Orbitalsmentioning
confidence: 99%